1996
DOI: 10.1007/s004390050158
|View full text |Cite
|
Sign up to set email alerts
|

Novel rhodopsin mutation in an autosomal dominant retinitis pigmentosa family: phenotypic variation in both heterozygote and homozygote Val137Met mutant patients

Abstract: A family affected with autosomal dominant retinitis pigmentosa (RP) is presented. Two clinically affected patients (mother and daughter) were heterozygous for the same novel missense mutation (Val137Met) of the rhodopsin gene (RHO). Both heterozygous and homozygous cases were observed among their few symptomatic relatives. Wide clinical variation was exhibited among the individuals with mutations in this family. None of the controls showed this change in RHO, nor has it been previously reported in other RP fam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

1997
1997
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 7 publications
0
9
0
Order By: Relevance
“…It is clear that there is never an overlap with the exception of site 137. Site 137 contains a V to M substitution that was originally reported to be associated with mild symptoms of ADRP (Ayuso et al, 1996). This substitution appears twice within vertebrates in lineages that are distantly related to humans (within the bonyfish lineage and in the branch leading to skates).…”
Section: Disease-causing Amino Acids Do Not Overlap With the Amino Acmentioning
confidence: 98%
“…It is clear that there is never an overlap with the exception of site 137. Site 137 contains a V to M substitution that was originally reported to be associated with mild symptoms of ADRP (Ayuso et al, 1996). This substitution appears twice within vertebrates in lineages that are distantly related to humans (within the bonyfish lineage and in the branch leading to skates).…”
Section: Disease-causing Amino Acids Do Not Overlap With the Amino Acmentioning
confidence: 98%
“…Among rhodopsin amino acids that when mutated cause ADRP (Briscoe, Gaur et al 2004), the conservation is only slightly higher (87% identity and 91% similarity). One amino acid substitution that causes ADRP in humans, V137M (Ayuso, Trujillo et al 1996), is found to occur in the wild-type Xenopus laevis sequence as in teleosts and skates (Briscoe, Gaur et al 2004). Note that the C-termini are the most divergent part of the sequences.…”
Section: Xenopus Laevis Expressing a P23h Rhodopsin Transgene Undergomentioning
confidence: 99%
“…This variable clinical expression among patients of a comparable age with the same gene defect appears to be common for many rhodopsin gene mutations. For instance, a conservative change at codon 137 (Val-137-Met) seems to produce only mild symptoms in some affected individuals [57] and mutation at codon 136 (Y136X) produces no apparent visual problems in younger individuals [58]. Patients carrying a Pro-347-Arg mutation show less severe disease and below the age of 40 do not develop retinal hyperpigmentation [59] whereas patients with a Pro-347-Leu mutation display a significantly smaller visual field area, more extensive impairment and a range of abnormality among different patients [60].…”
Section: Reviewsmentioning
confidence: 99%